As dinâmicas da produção da farinha de mandioca (Manihot esculenta Crantz) em uma comunidade quilombola, Abaetetuba, Pará, Brasil - SANTOS, Aldalena do Socorro da Costa dos (2019)
The objective of this study was to analyze the factors and decision processes related to the production of manioc flour (Manihot esculenta Crantz) in the quilombola community Sacred Heart of Jesus, Rio Genipaúba, Abaetetuba - Pa. A socioeconomic diagnosis was made of the establishments involved in the production of cassava flour, which made it possible to identify the social, economic, environmental and cultural factors and processes that are taken into account to decide to oscillate or even abandon production. The work was based on participatory research, since one of the authors is part of the community, interacting during the production processes. As data collection tools, we used semi-structured questionnaire interviews, with open and closed questions, applied to 10 (ten) farmers. As main results, it was found that in the community these families live from diverse activities in agriculture (cassava planting, açaí cultivation, cupuaçu planting, piquiá, chestnut, banana, etc.), besides non-agricultural activities, both activities influence decision-making processes. It also highlights processes of technological change. In addition, some changes in the availability of cassava planting area, which are destined for açai or other productive activities, are competing for area or also for the direct participation of the family's workforce. However, there are indications of a return to the increase in production, even if not very expressive for trade, but very significant for food and nutritional security, driven mainly by the increase in the price of good quality flour in the local market. It is concluded that the factors that influence the decision-making process are related to the direct participation of the family's workforce; the consumption habits, the need and quality of production and the lack of financial conditions to work and support the family.